Pemberdayaan Masyarakat Melalui Pelatihan Akuntansi dan Digitalisasi di Banjar Gagah Desa Tegallalang - I Wayan Chandra Adyatma; I Kadek Agus Mahabojana Dwi Prayoga; I Made Dwi Sumba Wirawan (Institut Teknologi dan Bisnis Semarang, 2024)
Tegallalang Village, located in Gianyar Regency, Bali Province, Indonesia, has become an attractive tourist destination due to its natural and cultural uniqueness. Situated in the northern part of Gianyar Regency and bordering several other villages, including Ubud Subdistrict to the south, Tegallalang Village plays an important role as a supporting village for tourism in the Ubud area. However, the development of community-based tourism in Banjar Gagah, Tegallalang Village, faces two main issues: suboptimal business management due to traditional administrative and financial recording systems, and the underutilization of tourism potentials such as agro-tourism, handicraft centers, and natural attractions. The stages of the community service activities are well-structured. It begins with the preparation stage, which involves coordination between the proposing team, the implementers, and the partners. The planning stage includes the preparation of event schedules, meetings with partners, the formation of a support team, and the preparation of outreach materials. The implementation stage is conducted in several sessions, starting with the first visit during the outreach and training sessions. Periodic evaluations are conducted about three months after the training to monitor the partners' progress in applying the knowledge and skills acquired. As such, this community service activity is expected to have a significant positive impact on the development of tourism, the local economy, as well as the preservation of culture and nature in Tegallalang Village.